Employee Admissions Information System Web-based at CV Galerindo Nusantara - Edy Susena; Edy Susanto; Dwi Iskandar; Muhamad Handi Stiawan (International Journal of Computer and Information System (IJCIS), 2021)
CV Galerindo Nusantara company still uses manual methods in the recruitment process, namely prospective employees must come to the company to apply for work and still use paper so that companies need a computerized system that can facilitate employee recruitment activities. Based on these problems the authors seek solutions to make it easier for companies to overcome these problems. In developing this system, the author uses the waterfall method, namely the work of a system that is carried out sequentially or linearly. The results of the web-based employee recruitment information system at CV Galerindo Nusantara which was created by the author are to produce a system that can make it easier for prospective employees and companies to carry out computerized employee recruitment activities as well as time efficiency and make it easier for prospective employees to access information systems.